The relationship between retinal nerve fibre layer thickness and total retinal blood flow in primary open angle claucoma - Flanagan, John G; Yusof @ Alias, Firdaus; Cheng, Richard; Tayyari, Faryan; Espahbodi, Nadia; Khuu, Lee-Anne; M Buys, Yvonne; Trope, Graham; Hudson, Christopher (Association for Research in Vision and Ophthalmology, 2014)
Purpose: To investigate the relationship between Doppler SD-OCT derived retinal blood flow (RBF) and the retinal nerve fiber layer (RNFL) thickness in patients with primary open angle glaucoma (POAG) and healthy age-matched controls.